2005
DOI: 10.1007/s00299-005-0010-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficient plant regeneration from leaves of rapeseed (Brassica napus L.): the influence of AgNO3 and genotype

Abstract: Factors influencing reliable shoot regeneration from leaf explants of rapeseed (Brassica napus L.) were examined. Addition of AgNO(3) to callus induction medium was significantly effective for shoot regeneration in all three genotypes initially tested. When 48 genotypes subsequently were surveyed, a large variation of shoot regenerability was observed, ranging from 100 to 0% in frequency of bud formation and from 7.5 to 0 in the number of buds per explant. A significant correlation (r=0.84) was observed betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 22 publications
7
26
0
Order By: Relevance
“…It remains to be shown whether these shoots develop directly or indirectly from mesophyll cells or vascular parenchyma in cauliflower, given that several studies have shown that brassica adventitious shoots arise from vascular parenchyma cells in seedling and leaf explants (e.g. Hachey et al, 1991;Mukhopadhyay et al, 1992;Sharma et al, 1993;Akasaka-Kennedy et al, 2005). This is interesting as plastid transformants of B. oleracea have been regenerated from leaf explants after biolistics delivery of plasmid DNA (Liu et al, 2007).…”
Section: Shoot Regeneration From Leaf Explants Of Cauliflower Cultivarsmentioning
confidence: 99%
“…It remains to be shown whether these shoots develop directly or indirectly from mesophyll cells or vascular parenchyma in cauliflower, given that several studies have shown that brassica adventitious shoots arise from vascular parenchyma cells in seedling and leaf explants (e.g. Hachey et al, 1991;Mukhopadhyay et al, 1992;Sharma et al, 1993;Akasaka-Kennedy et al, 2005). This is interesting as plastid transformants of B. oleracea have been regenerated from leaf explants after biolistics delivery of plasmid DNA (Liu et al, 2007).…”
Section: Shoot Regeneration From Leaf Explants Of Cauliflower Cultivarsmentioning
confidence: 99%
“…We next establish molecular assays of clock function, exploiting clock-regulated promoter:LUCIF-ERASE reporters. Agrobacterium tumefaciens-mediated transformation through explant-based callus cocultivation is an efficient method for many Brassica species and varieties, including Brassica napus, B. oleracea, and Brassica juncea (De Block et al, 1989;Akasaka-Kennedy et al, 2005;Arumugam et al, 2007;Bhalla and Singh, 2008). However, efforts to generate transgenic plants of B. rapa have been less successful, limited by low regeneration and rooting rates from callus and also by the inefficiency of vacuum infiltration (Zhang et al, 2000;Xu et al, 2008).…”
mentioning
confidence: 99%
“…Heritability in the broad and narrow sense was analyzed, respectively, amounting to 0.973 and 0.819 values. Akasaka-Kennedy et al (2005) demonstrated a genetic control of the shoot formation ability for winter oil- Table 4. Heritability in the broad and narrow sense obtained for the four studied traits Trait Heritability in the broad sense Heritability in the narrow sense…”
Section: Resultsmentioning
confidence: 99%